Cleavage theory meets civil society: a framework and research agenda - Mierke-Zatwarnicki, Alex; Borbáth, Endre; Hutter, Swen (West European politics, 2026)
How does civil society shape the development of cleavages? While intermediary organisations, such as trade unions and churches, featured heavily in historical accounts, neo-cleavage theory tends to ignore the meso-level dynamics of the new ‘transnational’ divide beyond party politics. This agenda-setting article introduces a general framework for studying the relationship between civil society and cleavages, capable of facilitating comparisons across contexts. Specifically, the article identifies two mechanisms through which civil society - in different forms - can shape emerging cleavages: by structuring patterns of group-party linkage on the supply-side and by deepening social closure on the demand-side. The article develops hypotheses about how the changing structure of civil society in Western Europe affects its capacity to perform these functions. Empirical evidence from expert and population surveys, complemented by illustrative case studies, suggests that civil society continues to influence cleavage politics, albeit in more differentiated and volatile ways.